Entrepreneurial quality: some evidence from Greek public policy - Oikonomakos, P.; Voukoutis, L; Tsipouri, L. (MIBES Transactions, 2017)
The present paper tries to devise a rating system for evaluating the likelihood of success of publicly supported companies. In recent literature we encounter quality indexes, composed of variables like name selection, registration location, intellectual property rights etc., which predict fairly accurately startup success. Unfortunately such indexes can only be compiled for countries with open administrations facilitating access and cross-checking of company data. We argue, however, that it is countries with less open administrations that have the highest need of ex ante quality assessment in order to maximise the public return of investment of state support mechanisms. This is why we suggest that, rather than giving up research on the likelihood of company growth because of lack of systematic open data, we can test firm dynamism based on public domain information. Dynamic firms, we assume, will be more likely to grow. The Web and Social Media data, which have until now mostly been used for marketing purposes, can be a valuable source of information for our purpose. We attempted to use the digital footprint as a proxy for the dynamism of SMEs and startups. Using State Aid schemes (i.e. public support to profit-oriented companies) in the period 2007-2013 in Greece we constructed a sample of 2000 companies and rated them individually for their presence (or not) in Facebook, LinkedIn, a site (with or without registered domain name), e-mail with domain name, references, size of the site, sales via web, search function, communication, regular update, FAQs and after sales support availability. Testing for sector, region, type of company and type of support scheme we find a statistically significant result for the more dynamic sectors, type of schemes and type of companies, while the regional level appears to be irrelevant, as companies in all regions demonstrate a fairly unified digital presence.